Islamisasi Ilmu Pengetahuan Dan Konsep Integrasi Ilmu Dalam Pemikiran Ismail Raji Al-Faruqy - Ridwan, Muhammad; Saifullah, Saifullah; Saputra, Riki; Julhadi, Julhadi (Institut Agama Islam Sumatera Barat Pariaman, 2025)
Many of the scientific assertions that originated in the West and culminated there have also led to breakthroughs in critical thinking from a number of Muslim thinkers and academics. Examples include Ismail Raji Al-Faruqi, who created the idea of Islamisation of science as a real step in reconstructing and dismantling a number of globally stigmatised statements. The purpose of this research is to find out how the Islamisation of science and the idea of science integration in the thought of Ismail Raji Al-Faruqi. This research uses qualitative methods with analytical descriptive techniques in certain types of library research. The concepts or thoughts of Ismail Raji Al-Faruqi as outlined in writings, both in his own works and the works of others, are used as data sources examined in this study. The rise of modern science is an indication of the phenomenon of the rapid progress of science. Muslims are greatly affected by this phenomenon. This is because science has led to the decline of morals and ethics that are not rooted in Islam. Thus, Islam is recognised as a true religion that upholds moral principles. Thus, Ismail Raji Al-Faruqi, a Muslim academic who pioneered the concept of Islamisation of science, expressed his critical views.